Generation of the induced pluripotent stem cell line LEIi023-A from a rod-cone dystrophy patient carrying the dominant PRPF31 c.267del variant - Dan Zhang; Di Huang; Shang-Chih Chen; Danial Roshandel; Tina M Lamey; Jennifer A Thompson; Terri L McLaren; Fred K Chen; Samuel McLenachan (Stem Cell Research)
The human induced pluripotent stem cell line LEIi023-A was generated from a 51-year-old female patient with retinitis pigmentosa 11 (RP11) caused by a single nucleotide deletion in the PRPF31 gene, (NM 015629.3: c.267del, p.(Glu89Aspfs*11)). Reprogramming the patient dermal fibroblasts was performed using episomal plasmids expressing reprogramming factors: OCT4, SOX2, KLF4, LMYC, LIN28, p53 shRNA and miR-302/367. LEIi023-A displayed expression of pluripotent stem cell markers, a normal karyotype and capability for differentiation of the three germ layers and retinal pigment epithelial cells.